Food Buying and Selling without Halal Labels: Case Review in BPJPH of South Sumatera - Bobby, Muhammad; Rahmadani, Adela (Sekolah Tinggi Agama islam Negeri Majene, 2024)
This study has conducted a small survey at the mini market in Palembang. There are so many foods in circulation that do not yet have a halal label and there are also foods that are labelled halal but contain many dangerous ingredients. This case should be questioned to the Halal Product Guarantee Agency known as BPJPH so that the aim of this study is to examine the legality of purchasing and selling non-halal food products and demonstrate it under the perspective of Sharia Economic Law. In this study, field research was used, using data through interviews with related parties and collecting documentation, then the data was built and analysed using qualitative research methods. The finding of the study discloses that the opinion of the Halal Product Guarantee Agency of the Ministry Religious Affairs in South Sumatera, still allows food that has not been halal-labelled to be sold. Products that do not yet have a halal certificate are not immediately punished but are still given the opportunity to take care of halal certification until 17 October 2024 and have been regulated in Article 33 of the Law of the Republic of Indonesia No. 33 of 2014. The Halal Product Guarantee policy is needed by the community. Therefore, the government continues to strive to accelerate Halal Certification, especially MSME perpetrators. Also, this certification aims to benefit the community so that they consume food and drinks that have legal certainty.